Eco-environmental water consumption due to changes in wetland areas a case study of the Liaohe River Delta, China - Jialin, Li (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2010)
Water plays an important role in the ecological evolution of the wetlands. The study of eco-environmental water consumption (EEWC) of the wetlands has become the emphasis and imperative issue in the restoration and the reconstruction of the wetland ecosystem. Based on the definition of EEWC, the methods of calculating the different components Of EEWC were determined. in a case study of the Liaohe River Delta in China, We analyzed the composition of the EEWC of various wetlands and the effects of changes in wetland areas and changes in wetland type on EEWC from 1988 to 2001 using remote sensing and ecological function analysis. The EEWC components included water consumption for wetland vegetation (WGWV), water consumption for wetland soil (WCWS), water consumption for wildlife habitat (WCWH), water consumption for groundwater replenishment (NCGR) water consumption for lake-pond-reservoir e ecosystem and fields for aquaculture (CLEFA) water consumption for estuary ecosystem (WCEE), water consumption for contamination purification (WCCP) and basic water consumption for river ecosystem (BWCRE). WCWV, WCWS and WCGR were important components of eco-environmental water requirements in the delta, accounting for more than 55% of the total amount of EEWC The change in gross eco-environmental water requirement was not obvious, being less than 3% of the total amount of EEWC from 1988 to 2001. The reed field had the largest number of water consumption types in the delta, followed by paddy fields, river-canal, lake-pond-reservoir, fields for aquaculture and water consumption of the upper-tidal flats. EEWC of river-canal per unit area was the highest among all the wetlands, followed by lake-pond-reservoir, fields for aquaculture, paddy fields, reed fields and upper-tidal flats. Because of changes in the wetland areas, changes in water consumption of various wetlands were comparatively complex. The amount of water used for ecological purposes in the area was less than the minimum EEWC. The problem of eco-environment in the wetlands was serious; thus the need to control and adjust water development and utilization to eliminate potential problems and to avoid degradation of the wetlands.